1998
DOI: 10.1152/ajpendo.1998.275.1.e6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma growth hormone secretion is impaired in obesity-prone rats before onset of diet-induced obesity

Abstract: Sprague-Dawley rats, which become obese (obesity prone) when fed a moderately high-fat (MHF; 32.5% of kcal as fat) diet, have decreased growth hormone (GH) concentrations compared with obesity-resistant rats fed the same diet. To determine whether plasma GH concentrations are different in obesity-prone rats compared with obesity-resistant rats before diet-induced obesity occurs, total integrated GH concentrations were determined in male Sprague-Dawley rats before exposure to the MHF diet. After initial blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
0
24
0
4
Order By: Relevance
“…28 The previous study indicated that the secretion of growth hormones has been shown to be impaired before the onset of a high-fat diet in obesity-prone rats. 31 Growth hormones might induce fast-to-slow transformation of muscle fibre type composition. 32,33 It is possible that the impairment of growth hormone secretion induced both body fat accumulation and fibre type transformation in obesity-prone rats in the study of Abou Mrad et al 28 In the present study, FFDR had higher CS and HAD activities than CR in the M. plantaris but not in the M. gastrocnemius or soleus.…”
Section: Discussionmentioning
confidence: 99%
“…28 The previous study indicated that the secretion of growth hormones has been shown to be impaired before the onset of a high-fat diet in obesity-prone rats. 31 Growth hormones might induce fast-to-slow transformation of muscle fibre type composition. 32,33 It is possible that the impairment of growth hormone secretion induced both body fat accumulation and fibre type transformation in obesity-prone rats in the study of Abou Mrad et al 28 In the present study, FFDR had higher CS and HAD activities than CR in the M. plantaris but not in the M. gastrocnemius or soleus.…”
Section: Discussionmentioning
confidence: 99%
“…Assignment of rats into obesity-prone (OP, nϭ6) and obesity-resistant (OR, nϭ6) groups was performed as previously described. 24,25 In brief, construction of body-weight-gain histograms was performed at the end of the study for MHF and LF diet groups. OR rats were defined as those with weight gains equal to or less than the heaviest controls, and the OP rats, as those with greater weight gains.…”
Section: · Dmentioning
confidence: 99%
“…These markers of obesity include initial weight gain during the first few days on a high-fat diet, 1,8 levels of leptin after a single high-fat meal in rats maintained on a lab chow diet, 9 meal-induced release of insulin 10 and fasting levels of triglycerides or basal growth hormone secretion in rats on chow. 11,12 While still at normal weight, the OP rats are found to exhibit a phenotype that has similarities to that seen in adult rats after they have become obese. [7][8][9][13][14][15][16] This phenotype in OP animals on a high-fat diet includes a small elevation of insulin, leptin, triglycerides and glucose, reduced sensitivity to insulin and leptin administration, and reduced capacity in muscle to metabolize fat.…”
Section: Introductionmentioning
confidence: 95%